Neosporosis in Argentina: Past, present and future perspectives - Campero, Lucia Maria (2023)
Neosporosis, caused by the protozoan Neospora caninum, was first diagnosed in Argentinean cattle in the 90's. With a national bovine stock of approximately 53 million head, the cattle industry is socially and economically relevant. Severe economic losses have been estimated at US$ 33 and 12 million annually in dairy and beef cattle, respectively. Approximately 9% of bovine abortions in the Buenos Aires province are caused by N. caninum. In 2001, the first isolation of N. caninum oocysts from feces of a naturally infected dog was performed in Argentina and named as NC-6 Argentina. Further strains were isolated from cattle (NC-Argentina LP1, NC-Argentina LP2) and axis deer (Axis axis, NC-Axis). Epidemiological studies revealed a high distribution of Neospora-infections not only in dairy but also in beef cattle, with seroprevalence rates of 16.6–88.8% and 0–73%, respectively. Several experimental infection studies in cattle have been carried out, as well as attempts to develop effective vaccines to avoid Neospora-abortions and transmission. However, no vaccine has proven successful for its use in daily practice. Reduction of seroprevalence, vertical transmission and Neospora-related abortions have been achieved in dairy farms by the use of selective breeding strategies and embryo transfer. Neospora-infections have been also detected in goats, sheep, deer, water buffaloes (Bubalus bubalis) and gray foxes (Lycalopex griseus). Moreover, Neospora-related reproductive losses were reported in small ruminants and deer species and could be more frequent than previously thought. Even though diagnostic methods have been improved during the last decades, control of neosporosis is still not optimal. The development of new strategies including new antiprotozoal drugs and vaccines is highly needed. This paper reviews the information from the previous 28 years of research of N. caninum in Argentina, including seroprevalence and epidemiological studies, available diagnostic techniques, experimental reproduction, immunization strategies, isolations and control measures in domestic and non-domestic animals from Argentina.